Novel approach for predicting the creep behavior of ceramic fibers using dimensional analysis - Berman, Renan Belli; Almeida, Renato Saint Martin; Azmah Hanim, Mohamed Ariff; de Pieri, Edson Roberto; Al‐Qureshi, Hazim Ali (John Wiley and Sons Inc, 2024)
A more generalized approach for predicting the steady-state creep rate of ceramic fibers under extensive stress ranges is proposed. Creep rate equations derived from dimensional analysis, such as Almeida's creep equation and Arrhenius’ creep equation, were evaluated using Buckingham's method, and the corresponding π groups were determined. Subsequently, a new equation is proposed using the usual semi-empirical constants for the diffusional and power law creep phenomena, along with an additional power law exponent to account for changes in creep mechanisms at higher stresses. The proposed equation was used to fit the creep rate data of the fiber Nextel 720 at various temperatures and constant stress, which demonstrated a good fit with an adjusted R-squared of.96. Subsequently, the equation was used to predict the creep rate at constant temperature and various stresses, exhibiting an adjusted R-squared of.77 and.85, depending on the scatter of the used data. The predictive results of the proposed equation were then compared to those obtained using the Arrhenius creep equation, which tends to higher rates at high stresses. In summary, the novel equation can be more efficiently applied in predicting the creep rate of ceramic fibers across a broader spectrum of stress.